Validity Criteria of Pretrial Detention: An Analysis of Judicial Errors - Kasimov, A.A. (Bulletin of the Karaganda University “Law Series”, 2026)
The purpose of this study is to provide a comprehensive analysis of the legal and practical criteria for the validity of pretrial detention and to identify typical judicial errors in the application of this measure. The methods include a systematic analysis of criminal procedure legislation, a comparative method, and a statistical analysis of judicial practice. Particular attention is paid to the regulatory resolutions of the Supreme Court of Kazakhstan and to the legal positions of the ECHR in assessing the validity of suspicion and the risks of obstructing justice. The findings demonstrate a persistent trend toward the excessive use of the most stringent coercive measure. The author reveals that the key issues include a formalized approach, manifested in the rubber-stamping of prosecution arguments, and the arbitrariness of assessments, where the severity of the charge becomes the sole and decisive factor for arrest. The article provides a classification of typical errors, ranging from the absence of specific factual data in case materials to the disregard of alternatives such as house arrest or bail. The conclusions emphasize the need for a transition from formalized to substantive judicial control when considering motions. The validity of detention must be supported by actual, not presumed, evidence of an intent to abscond or to destroy evidence. The recommendations may improve the procedural mechanism by minimizing cases of unjustified restrictions on personal liberty and overcoming inquisitorial bias in judicial practice.